Students’ Perceptions of Lumi Education for English Vocabulary Learning in a Semi-Rural High School - Strahayu Fadillah; Fatimah Hidayahni Amin; Ryan Rayhana Sofyan (International Journal of Language, Education, and Literature, 2026)
This study explores students’ perceptions of using Lumi Education as a learning tool for English vocabulary acquisition at SMAN 13 Sinjai. Data were collected using a 15-item Likert-scale questionnaire and semi-structured interviews with selected students. Quantitative analysis of the questionnaire provided descriptive insights into students’ attitudes, while qualitative thematic analysis of the interviews identified key themes, including engagement and enjoyment, design and visual appeal, clarity and comprehension, gamification and motivation, immediate feedback, active learning, and technical challenges. Overall, students reported positive perceptions, highlighting that interactive exercises and gamified activities enhanced their vocabulary learning experience, motivation, and participation. Some technical issues were noted, suggesting the need for improved infrastructure and guidance. The findings indicate that Lumi Education is an effective, engaging, and learner-centered tool that supports active and meaningful learning, providing practical insights for educators seeking to integrate digital platforms into language instruction.